Influence of donor pretreatment with dopamine on allogeneic kidney transplantation after prolonged cold storage in rats - Göttmann, Uwe; Notheisen, Anneke; Brinkkötter, Paul-Thomas; Yard, Benito A.; Waldherr, Rüdiger; Schnülle, Peter; Woude, Fokko J. van der; Braun, Claude (Transplantation, 2005)
BACKGROUND: Retrospective transplant database analysis revealed that administration of catecholamines to organ donors reduces acute rejection episodes and improves graft survival after renal transplantation. In the present study, the authors investigated the influence of dopamine donor pretreatment before prolonged cold storage on short- and long-term graft outcome after allogeneic kidney transplantation. METHODS: Fisher donor rats were treated intravenously for 24 hr with dopamine or isotonic saline, Lewis rats treated with saline served as controls. Explanted kidneys were stored for 24 hr at 4 degrees C in University of Wisconsin solution and transplanted into Lewis rats. RESULTS: Dopamine pretreatment markedly reduced the infiltration of monocytes down to the level of isogeneic controls 5 days after allogeneic transplantation and hastened recovery of renal function in the first days after transplantation. After 24 weeks, serum creatinine and proteinuria were significantly lower in recipients of dopamine-treated grafts. Histologically, dopamine donor pretreatment significantly reduced the severity of chronic allograft nephropathy. Survival of animals that underwent transplantation was improved by dopamine pretreatment of donors (P=0.04). CONCLUSIONS: Pretreatment of organ donors with dopamine improves short- and long-term outcome after prolonged cold storage and subsequent allogeneic kidney transplantation in rats. The authors' experimental data demonstrate that donor treatment is a simple and effective approach for preventing long-term graft loss after kidney transplantation.
Gesehen am 25.05.2022